Micrograph analysis of morphological alteration and cellular damage of fruit rot fungal pathogens treated with Averrhoa bilimbi fruit and Garcinia mangostana pericarp ethanolic extracts - Abd Murad, N. B.; Mustafa, M.; Shaari, K.; Mohd Zainudin, N. A. I. (Wiley-Blackwell Publishing, 2022)
The aim of this study is to assess the antifungal action of Averrhoa bilimbi fruit and Garcinia mangostana pericarp ethanolic extracts in altering the morphology and causing cellular damage of Fusarium oxysporum, Fusarium proliferatum, Colletotrichum gloeosporioides and Lasiodiplodia theobromae. The pathogens were cultured on media containing both extracts individually and carbendazim as positive control, whereas media alone as negative control. All samples were processed for microscopy observations using scanning (SEM) and transmission electron (TEM) microscopes. Observation via SEM showed significant alterations in the hyphae of F. oxysporum, F. proliferatum and C. gloeosporioides compared to the control in which the hyphae were in normal form. However, no significant alteration in hyphae had been observed in the treated plate compared to the control for L. theobromae. The development of calcium carbonate crystals was also observed abundantly in control compared to treated pathogens for F. oxysporum and F. proliferatum only. This indicated that the plant extracts can inhibit some metabolic processes in the pathogens too. Observations via TEM had been conducted for F. proliferatum and C. gloeosporioides, respectively. The results showed disintegration of cytoplasmic organelles and cell wall, intense vacuolization and lyses part of fungal cells. The plant extracts have equivalent or even greater effects compared to commercial fungicide carbendazim.